Potential Use of I. suffruticosa in Treatment of Tuberculosis with Immune System Activation - Carli, Camila Bernardes de Andrade; Quilles, Marcela Bassi; Maia, Danielle Cardoso Geraldo; Leite, Clarice Q. Fujimura; Vilegas, Wagner; Carlos, Iracilda Z. (IntechOpen, 2012)
None